2018
DOI: 10.3892/br.2018.1108
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB2 signalling modulates the neural differentiation of human dental pulp stem cells

Abstract: Dental pulp stem cells (DPSCs) originate from the embryonic neural crest and have neurogenic potential. The present study investigated the roles of the forward and reverse EphrinB2 signalling pathways during DPSC neurogenesis. Treatment of DPSCs with recombinant EphrinB2-Fc protein over 7 days in a neural induction culture resulted in significant downregulation of the following neural markers: βIII-Tubulin, neural cell adhesion molecule (NCAM), nestin, neurogenin 2 (NGN2), neurofilament medium polypeptide and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…25 A previous study suggested that stimulation of reverse EphB4-EphrinB2 signalling marginally enhanced the neural differentiation of dental pulp stem cells. 6 These results offer an explanation for the directional differentiation of EphrinB2/BMSCs into neuron-like cells.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…25 A previous study suggested that stimulation of reverse EphB4-EphrinB2 signalling marginally enhanced the neural differentiation of dental pulp stem cells. 6 These results offer an explanation for the directional differentiation of EphrinB2/BMSCs into neuron-like cells.…”
Section: Discussionmentioning
confidence: 78%
“…5 Currently, there are limited reports on the roles of EphB4 and EphrinB2 in stem cells. 6 Similar to other tyrosine kinase receptors, signal transduction between EphB4 and EphrinB2 is bidirectional, as each can be activated by the other, producing ‘forward signals’ and ‘reverse signals’. 3 Autophosphorylation of the receptor is initiated by EphrinB2, with phosphoinositide 3-kinase, Src, mitogen-activated protein kinases, Akt and other proteins mediating the cascade reaction, thus giving rise to what is known as a forward signal.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated that some, but not all, DPSC isolates were capable of responding to BMP-2 with corresponding changes to growth, viability, and cellular morphology. Moreover, these changes were associated with sDT DPSC isolates not expressing multiple MSC biomarkers, but rather one specific MSC marker -Nestin [30,31].…”
Section: Discussionmentioning
confidence: 98%
“…For example, many other studies of DPSC differentiation have evaluated 4, which are known transcription factors that may directly influence specific pathways related to cellular phenotypes [40,41]. However, the role of Nestin ap to have been evaluated peripherally in studies of DPSC and neural differentiation without evaluation of this biomarker among studies of osteogenic differentiation and BMP administration [42,43]. These biomarkers may be critical indicators not only of differentiation status and may also directly or indirectly affect other phenotypic behaviours observed in this study, such as doubling time.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that dental and oral-derived stem cells also possess a high propensity to differentiate into the osteo-odontogenic lineage, which could in turn compromise their neurogenic differentiation capacity. Hence, previous studies have investigated various strategies to enhance the neural differentiation of these adult cells, involving supplementation of various growth factors and small molecules within the culture milieu, 5 recombinant gene expression, 6 utilization of various novel scaffold materials, 7 , 8 together with the application of physical stimuli such as ultrasound. 8 …”
Section: Introductionmentioning
confidence: 99%